Impact of Common Iliac Vein Compression on the Incidence of Pulmonary Embolism in Patients with Acute Deep Vein Thrombosis - Shi, Yadong; Yuan, Yuan; Kong, Jie; Su, Haobo; Chen, Liang; Huang, Hao; Lu, Zhaoxuan; Gu, Jianping (European journal of vascular and endovascular surgery, 2023)
This study aimed to investigate the association between common iliac vein (CIV) compression and pulmonary embolism (PE) in lower extremity deep vein thrombosis (DVT). This was a single centre retrospective study. Between January 2016 and December 2021, DVT patients with enhanced computed tomography of the iliac vein and pulmonary artery were included. Patient demographics, comorbidities, risk factors, and degree of CIV compression were collected and analysed. Logistic regression was performed to evaluate the odds ratio (OR) with a 95% confidence interval (CI) of PE in relation to compression severity groups. The association between PE and compression degree was evaluated with restricted cubic splines (RCS) based on an adjusted logistic regression model. Two hundred and twenty-six DVT patients (left side, n = 153; right side, n = 73) were included. Univariable analyses suggested that symptomatic or asymptomatic PE (54.4%, 123/226) was more common in men (p = .048) and right side DVT (p = .046) patients. Compared with no CIV compression, multivariable analyses suggested that mild compression did not statistically significantly reduce the PE risk, whereas moderate (adjusted OR 0.36; 95% CI 0.15 – 0.88; p = .025) and severe (adjusted OR 0.18; 95% CI 0.06 – 0.54; p = .002) compression statistically significantly reduced the risk. RCS showed that a smaller minimum diameter or greater compression percentage was correlated with continuously decreasing PE risk at a minimum diameter of < 6.77 mm or compression > 42.9%. PE is more common in men and right side DVT patients. An increasing severity of CIV compression is consistently associated with a decreasing risk of PE when the minimum diameter is < 6.77 mm or the compression is > 42.9%, indicating that it is a protective factor against PE.